Hot-rolled steel sheet

By adjusting the chemical composition and metal structure of the hot-rolled steel plate, the problems of insufficient reduction in the limit fracture plate thickness, shear processing and corrosion resistance of the hot-rolled steel plate in the prior art are solved, and the effects of high strength and excellent forming are achieved, and are suitable for automotive components and other fields.

CN119855931APending Publication Date: 2025-04-18NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380065566.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-31
Filing Date
2023-10-23
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, there are shortcomings in the ultimate fracture plate thickness reduction rate, shear processing properties and corrosion resistance of hot-rolled steel plates, which are difficult to meet the demand for high strength and excellent formability in the fields of automotive components.

Method used

By adjusting the chemical composition and metal structure of the hot-rolled steel plate, it specifically includes controlling the content of elements such as C, Si, Mn, and Cr in the chemical composition, and optimizing the Entropy value, Inverse difference normalized value and Cluster Shade value of the metal structure through methods such as grayscale symbiosis matrix method to improve the ductility, shear workability and corrosion resistance of the steel plate.

Benefits of technology

The high strength and ultimate fracture plate thickness reduction rate of hot-rolled steel plate are achieved, and its ductility, shear processing and corrosion resistance are improved. It is suitable for automotive components and other industrial uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005308065160000041
    Figure BDA0005308065160000041
  • Figure BDA0005308065160000181
    Figure BDA0005308065160000181
  • Figure BDA0005308065160000182
    Figure BDA0005308065160000182
Patent Text Reader

Abstract

The present invention pertains to a hot-rolled steel sheet having a prescribed chemical composition, the metal structure at a position 1 / 4 from the surface in the sheet thickness direction having, in area%, less than 3.0% of retained austenite, 15.0% to less than 60.0% of ferrite, less than 5.0% of pearlite, an E value of 10.7 or more, an I value of 1.020 or more, a CS value of-8.0 * 105 to 8.0 * 105, and a standard deviation of Mn concentration of 0.60 mass% or less; in the surface, the number density of Si-Al-Cr oxides having an equivalent sphere radius of 0.500 [mu] m or more is 2.0 * 10 < 3 > / cm < 2 > or less, and the number density of Si-Al-Cr oxides having an equivalent sphere radius of 0.005-0.050 [mu] m is 1.0 * 10 < 5 > / cm < 2 > or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hot rolled steel plate.

[0002] This application claims priority based on Japanese patent application No. 2022-174630 filed on October 31, 2022, and the contents are cited here. Background Art

[0003] In recent years, from the perspective of protecting the global environment, many fields are trying to reduce carbon dioxide emissions. Even automobile manufacturers are actively developing technologies to reduce vehicle weight for the purpose of reducing fuel consumption. However, since the focus is also on improving collision resistance in order to ensure the safety of passengers, it is not easy to reduce the weight of the vehicle.

[0004] In order to balance the lightweight of the vehicle body with the collision resistance, the use of high-strength steel plates to make the components thinner is being studied. Therefore, there is an urgent need for steel plates that have both high strength and excellent formability, and several technologies have been proposed in the past to meet these requirements. There are various processing methods for automobile components, so the required formability varies depending on the component used. Among them, the limit fracture thickness reduction rate and ductility are positioned as important indicators of formability.

[0005] The so-called limit fracture thickness reduction rate is a value obtained from the minimum value of the plate thickness of the tensile test piece before fracture and the plate thickness of the tensile test piece after fracture. When the limit fracture thickness reduction rate is low, it is easy to fracture early when tensile strain is applied during press forming, which is not preferred.

[0006] Automobile parts are formed by press forming, but the blank sheets for press forming are often manufactured by shearing, which has high productivity. In the blank sheets manufactured by shearing, it is necessary to have excellent end surface accuracy after shearing.

[0007] For example, if the morphology of the end surface after shearing (sheared end surface) is a secondary sheared surface of sheared surface-fracture surface-sheared surface, the accuracy of the sheared end surface is significantly deteriorated.

[0008] Furthermore, steel sheets used for automobile parts are required to have better corrosion resistance.

[0009] For example, Patent Document 1 discloses a hot-rolled steel sheet which serves as a base material for a cold-rolled steel sheet having excellent surface properties after press working, in which the Mn segregation and P segregation in the center of the sheet thickness are controlled.

[0010] However, Patent Document 1 does not take into account the limit fracture thickness reduction rate, shear workability, and corrosion resistance of the hot-rolled steel sheet.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: International Publication No. 2020 / 044445

[0014] Non-patent literature

[0015] Non-patent document 1: J. Webel, J. Gola, D. Britz, F. Mucklich, Materials Characterization 144 (2018) 584-596

[0016] Non-patent literature 2: DL Naik, HU Sajid, R. Kiran, Metals 2019, 9, 546

[0017] Non-patent document 3: K. Zuiderveld, Contrast Limited Adaptive Histogram Equalization, Chapter VIII.5, Graphics Gems IV. P. S. Heckbert (Eds.), Cambridge, MA, Academic Press, 1994, pp. 474-485 Summary of the invention

[0018] Problems to be solved by the invention

[0019] However, Patent Document 1 does not take into account the limit fracture thickness reduction rate, shear workability, and corrosion resistance of the hot-rolled steel sheet.

[0020] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a hot-rolled steel sheet having high strength and ultimate fracture thickness reduction rate, as well as excellent ductility, shear workability and corrosion resistance.

[0021] Means for solving problems

[0022] The gist of the present invention is as follows.

[0023] (1) One aspect of the present invention relates to a hot-rolled steel sheet, wherein the chemical composition comprises, in mass %, the following:

[0024] C: 0.050~0.250%,

[0025] Si: 0.40-1.00%,

[0026] Mn: 1.00~1.50%,

[0027] Sol.Al: 0.100~0.500%,

[0028] Cr: 0.50~2.00%,

[0029] P: 0.100% or less,

[0030] S: 0.0300% or less,

[0031] N: 0.1000% or less,

[0032] O: 0.0100% or less,

[0033] Ti: 0~0.500%,

[0034] Nb: 0~0.500%

[0035] V: 0~0.500%、

[0036] Cu: 0-2.00%,

[0037] Mo: 0-1.00%,

[0038] Ni: 0-2.00%,

[0039] B: 0~0.0100%,

[0040] Ca: 0~0.0200%,

[0041] Mg: 0~0.0200%

[0042] REM: 0~0.1000%、

[0043] Bi: 0~0.0200%,

[0044] As: 0~0.100%,

[0045] Zr: 0-1.00%,

[0046] Co: 0-1.00%,

[0047] Zn: 0~1.00%,

[0048] W: 0-1.00%, and

[0049] Sn: 0~0.05%,

[0050] The remainder includes Fe and impurities;

[0051] Satisfying the following equations (A) and (B),

[0052] The metal structure at a position 1 / 4 from the surface in the thickness direction is expressed in area %,

[0053] Retained austenite is less than 3.0%,

[0054] Ferrite is 15.0% or more and less than 60.0%,

[0055] Pearlite is less than 5.0%,

[0056] The entropy value expressed by the following formula (1) obtained by analyzing the SEM image of the metal structure using a gray-level co-occurrence matrix method is 10.7 or more.

[0057] The inverse difference normalized value expressed by the following formula (2) is 1.020 or more.

[0058] The Cluster Shade value expressed by the following formula (3) is -8.0×10 5 ~8.0×10 5 ,

[0059] The standard deviation of the Mn concentration is 0.60 mass % or less;

[0060] In the surface, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more is 2.0×10 3 Pieces / cm 2 Below, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm is 1.0×10 5 Pieces / cm 2 above;

[0061] 0.060%≤Ti+Nb+V≤0.500% (A)

[0062] Zr+Co+Zn+W≤1.00% (B)

[0063] Wherein, each element symbol in the formula (A) and (B) represents the content of the element in mass %, and 0% is entered when the element is not contained;

[0064] Here, P(i, j) in the following equations (1) to (5) is a gray level co-occurrence matrix, L in the following equation (2) is the number of gray levels obtained in the SEM image, i and j in the following equations (2) and (3) are natural numbers from 1 to L, and μ in the following equation (3) is x and μ y They are expressed by the following formulas (4) and (5),

[0065] [Mathematical formula 1]

[0066] Entropy=-∑ j∑ j P(i,j)log(P(i,j)) (1)

[0067] [Mathematical formula 2]

[0068]

[0069] [Mathematical formula 3]

[0070] Cluster·Shade=∑ j ∑ j (i+j-μ x -μ y ) 3 P(i,j) (3)

[0071] [Formula 4]

[0072] μ x =Σ i Σ j i(P(i,j)) (4)

[0073] [Formula 5]

[0074] μ y =∑ i ∑ j j(P(i,j)) (5)

[0075] (2) The hot-rolled steel sheet according to (1) above, wherein the chemical composition may contain, in terms of mass%, selected from

[0076] Ti: 0.001~0.500%,

[0077] Nb: 0.001~0.500%

[0078] V: 0.001~0.500%,

[0079] Cu: 0.01-2.00%,

[0080] Mo: 0.01~1.00%,

[0081] Ni: 0.02-2.00%,

[0082] B: 0.0001~0.0100%,

[0083] Ca: 0.0005~0.0200%,

[0084] Mg: 0.0005~0.0200%,

[0085] REM: 0.0005~0.1000%、

[0086] Bi: 0.0005~0.0200%,

[0087] As: 0.001~0.100%,

[0088] Zr: 0.01~1.00%,

[0089] Co: 0.01~1.00%,

[0090] Zn: 0.01~1.00%,

[0091] W: 0.01 to 1.00%, and

[0092] Sn: 0.01 to 0.05% of one or more kinds thereof.

[0093] Effects of the Invention

[0094] According to the above aspects of the present invention, a hot-rolled steel sheet having high strength and ultimate fracture thickness reduction rate, as well as excellent ductility, shear workability and corrosion resistance can be obtained.

[0095] The hot-rolled steel sheet of the present invention is suitable as an industrial base material for automobile components, mechanical structural parts and building components. BRIEF DESCRIPTION OF THE DRAWINGS

[0096] Figure 1 This is an example of the sheared end surface of the hot-rolled steel sheet according to the example of the present invention.

[0097] Figure 2 This is an example of a sheared end surface of a hot-rolled steel sheet of a comparative example. DETAILED DESCRIPTION

[0098] The chemical composition and metal structure of the hot-rolled steel sheet of this embodiment will be described in more detail below. However, the present invention is not limited to the configuration disclosed in this embodiment, and various modifications can be made within the scope of the present invention.

[0099] In the following numerical ranges between "-", the lower limit and the upper limit are included in the range. In the numerical values ​​expressed as "lower than" or "exceed", the value is not included in the numerical range. In the following description, the % of the chemical composition is mass % unless otherwise specified.

[0100] Chemical composition

[0101] The chemical composition of the hot-rolled steel sheet according to the present embodiment contains, by mass%, C: 0.050-0.250%, Si: 0.40-1.00%, Mn: 1.00-1.50%, sol.Al: 0.100-0.500%, Cr: 0.50-2.00%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, and the remainder: Fe and impurities, and satisfies formula (A) (0.060%≤Ti+Nb+V≤0.500%).

[0102] Each element is described in detail below.

[0103] C: 0.050~0.250%

[0104] C can increase the area ratio of the hard phase and increase the strength of ferrite by combining with precipitation strengthening elements such as Ti, Nb, and V. When the C content is less than 0.050%, the desired strength cannot be obtained. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.055% or more, more preferably 0.060% or more, and further preferably 0.065% or more.

[0105] On the other hand, when the C content exceeds 0.250%, the area ratio of ferrite decreases, and the ductility of the hot-rolled steel sheet decreases. Therefore, the C content is set to 0.250% or less. The C content is preferably 0.150% or less.

[0106] Si: 0.40~1.00%

[0107] Si has the effect of promoting the formation of ferrite to improve the ductility of the hot-rolled steel sheet, and has the effect of solid solution strengthening ferrite to increase the strength of the hot-rolled steel sheet. In addition, Si has the effect of making the steel sound by deoxidation (suppressing the occurrence of defects such as pores in the steel). When the Si content is less than 0.40%, the effect based on the above-mentioned effect cannot be obtained. Therefore, the Si content is set to 0.40% or more. The Si content is preferably 0.50% or more, and more preferably 0.60% or more.

[0108] However, when the Si content exceeds 1.00%, the number density of oxides on the surface of the steel sheet increases, which deteriorates the chemical conversion treatability. In addition, ferrite is easily excessively generated, which reduces the strength. Therefore, the Si content is set to 1.00% or less. The Si content is preferably 0.90% or less, and more preferably 0.80% or less.

[0109] Mn: 1.00~1.50%

[0110] Mn has the effect of suppressing ferrite transformation and improving the strength of hot-rolled steel sheets. When the Mn content is less than 1.00%, the desired strength cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.10% or more, and more preferably 1.20% or more.

[0111] On the other hand, when the Mn content exceeds 1.50%, the effect of Cr contained as a quenching element overlaps, making it difficult to transform into ferrite. Therefore, the Mn content is set to 1.50% or less. The Mn content is preferably 1.45% or less, and more preferably 1.40% or less.

[0112] Ti: 0~0.500%

[0113] Nb: 0~0.500%

[0114] V: 0~0.500%

[0115] 0.060%≤Ti+Nb+V≤0.500%(A)

[0116] The symbol of each element in the above formula (A) represents the content of the element in mass %, and 0% is used when the element is not contained.

[0117] Ti, Nb and V are elements that precipitate finely in steel in the form of carbides and nitrides, and improve the strength of steel through precipitation strengthening. If the total content of Ti, Nb and V is less than 0.060%, these effects cannot be obtained. Therefore, the total content of Ti, Nb and V is set to be greater than 0.060%. In other words, the value of the middle side of the above formula (A) is set to be greater than 0.060%. In addition, it is not necessary to contain all of Ti, Nb and V, as long as any one of them is contained, and its content can be greater than 0.060%. The total content of Ti, Nb and V is preferably greater than 0.080%, and more preferably greater than 0.100%. The contents of Ti, Nb and V are preferably greater than 0.001%, respectively.

[0118] On the other hand, if the total content of Ti, Nb and V exceeds 0.500%, the workability of the hot-rolled steel sheet deteriorates. Therefore, the total content of Ti, Nb and V is set to 0.500% or less. In other words, the value of the middle side of the above formula (A) is set to 0.500% or less. Preferably, it is 0.300% or less, more preferably 0.250% or less, and further preferably 0.200% or less.

[0119] Sol.Al: 0.100~0.500%

[0120] Al, like Si, has the function of deoxidizing steel to make it sound, and has the function of promoting the formation of ferrite to improve the ductility of hot-rolled steel sheets. When the sol.Al content is less than 0.100%, the effects based on the above functions cannot be obtained. Therefore, the sol.Al content is set to 0.100% or more. The sol.Al content is preferably 0.200% or more.

[0121] On the other hand, when the sol.Al content exceeds 0.500%, the above effect is saturated and it is not economically preferable. Therefore, the sol.Al content is set to 0.500% or less. The sol.Al content is preferably 0.450% or less, more preferably 0.400% or less, and further preferably 0.350% or less.

[0122] In addition, the term "sol.Al" means acid-soluble Al, and refers to solid-solution Al existing in the steel in a solid-solution state.

[0123] Cr: 0.50~2.00%

[0124] Cr has the effect of improving the hardenability of hot-rolled steel sheets. In addition, Cr forms oxides with Si and Al. When the Cr content is less than 0.50%, the effect of improving hardenability cannot be obtained. In addition, Si-Al-Cr oxides cannot be preferably formed on the surface. Therefore, the Cr content is set to 0.50% or more. The Cr content is preferably 0.60% or more, more preferably 0.70% or more, and further preferably 0.80% or more.

[0125] On the other hand, when the Cr content exceeds 2.00%, the chemical conversion treatability of the hot-rolled steel sheet is significantly reduced. Therefore, the Cr content is set to 2.00% or less. The Cr content is preferably 1.80% or less, and more preferably 1.60% or less.

[0126] P: 0.100% or less

[0127] P is also an element that has the effect of improving the strength of the hot-rolled steel sheet by solid solution strengthening. Therefore, P can also be actively contained. However, P is an element that is easy to segregate. If the P content exceeds 0.100%, the reduction in the ductility of the hot-rolled steel sheet and the reduction rate of the ultimate fracture thickness caused by grain boundary segregation becomes significant. Therefore, the P content is set to 0.100% or less. The P content is preferably 0.030% or less. The lower limit of the P content does not need to be specifically stipulated and can also be 0%, but from the perspective of refining cost, it is preferably set to 0.001% or more.

[0128] S: 0.0300% or less

[0129] S forms sulfide inclusions in steel and reduces the ductility and ultimate fracture thickness reduction rate of the hot-rolled steel sheet. If the S content exceeds 0.0300%, the ductility and ultimate fracture thickness reduction rate of the hot-rolled steel sheet are significantly reduced. Therefore, the S content is set to 0.0300% or less. The S content is preferably 0.0050% or less. The lower limit of the S content does not need to be specifically specified and may be 0%, but from the viewpoint of refining cost, it is preferably set to 0.0001% or more.

[0130] N: 0.1000% or less

[0131] N has the effect of reducing the ductility and ultimate fracture thickness reduction rate of the hot-rolled steel sheet. When the N content exceeds 0.1000%, the ductility and ultimate fracture thickness reduction rate of the hot-rolled steel sheet are significantly reduced. Therefore, the N content is set to 0.1000% or less. The N content is preferably 0.0800% or less, more preferably 0.0700% or less, and further preferably 0.0100% or less. The lower limit of the N content does not need to be specifically specified and may also be 0%, but in the case of making the metal structure finer by containing one or more of Ti, Nb and V, in order to promote the precipitation of carbonitrides, the N content is preferably set to 0.0010% or more, and more preferably 0.0020% or more.

[0132] O: 0.0100% or less

[0133] If O is contained in a large amount in steel, it forms coarse oxides that become fracture starting points, causing brittle fracture and hydrogen cracking. Therefore, the O content is set to 0.0100% or less. The O content is preferably 0.0080% or less, and more preferably 0.0050% or less. The O content may be 0%, but in order to disperse a large amount of fine oxides during deoxidation of molten steel, the O content may be set to 0.0005% or more or 0.0010% or more.

[0134] The remainder of the chemical composition of the hot-rolled steel sheet of the present embodiment may also include Fe and impurities. In the present embodiment, the so-called impurities refer to impurities mixed from the ore, scrap steel or manufacturing environment as raw materials, and / or impurities allowed within the range that do not have adverse effects on the hot-rolled steel sheet of the present embodiment.

[0135] The hot-rolled steel sheet of the present embodiment may contain the following elements as optional elements in place of a portion of Fe. When these optional elements are not contained, the lower limit of the content is 0%. The optional elements will be described in detail below.

[0136] Cu: 0.01~2.00%

[0137] Mo: 0.01~1.00%

[0138] Ni: 0.02~2.00%

[0139] B: 0.0001~0.0100%

[0140] Cu, Mo, Ni and B all have the effect of improving the hardenability of the hot-rolled steel sheet. In addition, Cu and Mo have the effect of improving the strength of the hot-rolled steel sheet by precipitating in the form of carbides in the steel. Furthermore, Ni, when Cu is contained, has the effect of effectively suppressing the grain boundary cracks of the slab caused by Cu. Therefore, one or more of these elements may also be contained.

[0141] As mentioned above, Cu has the effect of improving the hardenability of hot-rolled steel sheets and the effect of improving the strength of hot-rolled steel sheets by precipitating in the form of carbides in steel at low temperatures. In order to more reliably obtain the effect based on the above-mentioned effects, the Cu content is preferably set to 0.01% or more, and more preferably set to 0.05% or more. However, when the Cu content exceeds 2.00%, grain boundary cracks sometimes occur in the slab. Therefore, the Cu content is set to 2.00% or less. The Cu content is preferably 1.50% or less, and more preferably 1.00% or less.

[0142] As described above, Mo has the effect of improving the hardenability of hot-rolled steel sheets and the effect of improving the strength of hot-rolled steel sheets by precipitating in the form of carbides in steel. In order to more reliably obtain the effects based on the above effects, the Mo content is preferably set to 0.01% or more, and more preferably to 0.02% or more. However, even if the Mo content is set to more than 1.00%, the effects based on the above effects are saturated, which is not economically preferred. Therefore, the Mo content is set to 1.00% or less. The Mo content is preferably 0.50% or less, and more preferably 0.20% or less.

[0143] As mentioned above, Ni has the effect of improving the hardenability of hot-rolled steel sheets. In addition, when Ni contains Cu, it has the effect of effectively suppressing the grain boundary cracks of the slab caused by Cu. In order to more reliably obtain the effect based on the above-mentioned effect, the Ni content is preferably set to 0.02% or more. Since Ni is an expensive element, it is not economically preferable to contain a large amount of Ni. Therefore, the Ni content is set to 2.00% or less.

[0144] As mentioned above, B has the effect of improving the hardenability of hot-rolled steel sheets. In order to more reliably obtain the effect based on this effect, it is preferred that the B content be set to 0.0001% or more, and more preferably to 0.0002% or more. However, when the B content exceeds 0.0100%, the formability of the hot-rolled steel sheet is significantly reduced, so the B content is set to 0.0100% or less. The B content is preferably set to 0.0050% or less.

[0145] Ca: 0.0005~0.0200%

[0146] Mg: 0.0005~0.0200%

[0147] REM: 0.0005~0.1000%

[0148] Bi: 0.0005~0.0200%

[0149] Ca, Mg and REM all have the effect of improving the ductility of hot-rolled steel sheets by adjusting the shape of inclusions in steel to a preferred shape. In addition, Bi has the effect of improving the ductility of hot-rolled steel sheets by refining the solidification structure. Therefore, one or more of these elements may also be contained. In order to more reliably obtain the effect based on the above-mentioned effects, it is preferred to set the content of any one or more of Ca, Mg, REM and Bi to 0.0005% or more. However, if the Ca content or the Mg content exceeds 0.0200%, or the REM content exceeds 0.1000%, inclusions are excessively generated in the steel, which sometimes reduces the ductility of the hot-rolled steel sheet. In addition, even if the Bi content is set to more than 0.0200%, the effect based on the above-mentioned effect is saturated, which is not economically preferred. Therefore, the Ca content and the Mg content are set to less than 0.0200%, the REM content is set to less than 0.1000%, and the Bi content is set to less than 0.0200%. The Bi content is preferably less than 0.0100%.

[0150] Here, REM refers to a total of 17 elements including Sc, Y and lanthanoid elements, and the above REM content refers to the total content of these elements. In the case of lanthanoid elements, they are added industrially in the form of misch metals.

[0151] As: 0.001~0.100%

[0152] As contributes to improving the ductility of the hot-rolled steel sheet by lowering the austenite transformation temperature and refining the prior austenite grains. In order to reliably obtain this effect, the As content is preferably set to 0.001% or more.

[0153] On the other hand, even if a large amount of As is contained, the above-mentioned effect is saturated, so the As content is made 0.100% or less.

[0154] Zr: 0.01~1.00%

[0155] Co: 0.01~1.00%

[0156] Zn: 0.01~1.00%

[0157] W: 0.01~1.00%

[0158] Zr+Co+Zn+W≤1.00%(B)

[0159] Sn: 0.01~0.05%

[0160] The symbol of each element in the above formula (B) represents the content of the element in mass %, and when the element is not contained, it is entered as 0.

[0161] Regarding Zr, Co, Zn and W, the inventors of the present invention have confirmed that even if these elements are contained in a total of less than 1.00%, the effect of the hot-rolled steel sheet of the present embodiment is not impaired. Therefore, one or more of Zr, Co, Zn and W may be contained in a total of less than 1.00%. In other words, the value on the left side of the above formula (B) may also be set to less than 1.00%. Since Zr, Co, Zn and W may not be contained, the content of each may also be 0%. In order to make the steel plate solid solution strengthened and improve the strength, the content of Zr, Co, Zn and W may also be more than 0.01% respectively.

[0162] In addition, the inventors have confirmed that even if Sn is contained in a small amount, the effect of the hot-rolled steel sheet of the present embodiment will not be impaired. However, if Sn is contained in a large amount, defects sometimes occur during hot rolling, so the Sn content is set to 0.05% or less. Since Sn may not be contained, the Sn content may also be 0%. In order to improve the corrosion resistance of the hot-rolled steel sheet, the Sn content may also be set to 0.01% or more.

[0163] The chemical composition of the hot-rolled steel sheet can be measured by conventional analytical methods. For example, ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) can be used for measurement. In addition, sol.Al can be measured by ICP-AES using the filtrate after the sample is heated and decomposed with acid. C and S can be measured by the combustion-infrared absorption method, N can be measured by the inert gas melting-thermal conductivity method, and O can be measured by the inert gas melting-non-dispersive infrared absorption method.

[0164] When the hot-rolled steel sheet has a coating on its surface, the coating may be removed by mechanical grinding or the like as necessary, and then the chemical composition may be analyzed.

[0165] Metal structure of hot rolled steel plate

[0166] Next, the metal structure of the hot-rolled steel sheet according to the present embodiment will be described.

[0167] In the hot-rolled steel sheet of the present embodiment, the metal structure at a position 1 / 4 from the surface in the plate thickness direction has, in terms of area %, less than 3.0% of retained austenite, more than 15.0% of ferrite and less than 60.0% of pearlite, and less than 5.0% of pearlite. The Entropy value expressed by the following formula (1) obtained by analyzing the SEM image of the metal structure using the gray level co-occurrence matrix method is 10.7 or more, the Inverse difference normalized value expressed by the following formula (2) is 1.020 or more, and the Cluster Shade value expressed by the following formula (3) is -8.0×10 5 ~8.0×10 5 The standard deviation of the Mn concentration is 0.60 mass % or less, and the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more on the surface is 2.0×10 3 Pieces / cm 2 Below, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm is 1.0×10 5 Pieces / cm 2 above.

[0168] Therefore, the hot-rolled steel sheet of the present embodiment can obtain high strength and ultimate fracture thickness reduction rate, as well as excellent ductility, shear workability, and corrosion resistance.

[0169] In addition, in this embodiment, the structure fraction, entropy value, inverse difference normalized value, cluster shade value and standard deviation of Mn concentration of the metal structure in the region 1 / 4 from the surface in the plate thickness direction are specified because the metal structure in this position represents a representative metal structure of the steel plate.

[0170] In addition, the so-called "surface" here refers to the interface between the coating and the steel plate when the hot-rolled steel plate has a coating, and the so-called "position at a depth of 1 / 4 from the surface" refers to a position at a depth of 1 / 4 of the thickness of the plate along the thickness direction from the surface of the hot-rolled steel plate.

[0171] Area ratio of retained austenite: less than 3.0%

[0172] Retained austenite is a metal structure that exists as a face-centered cubic lattice even at room temperature. Retained austenite has the effect of improving the ductility of hot-rolled steel sheets through transformation induced plasticity (TRIP). On the other hand, retained austenite transforms into high-carbon martensite during processing, thus becoming the starting point of cracks during deformation and the reason for the reduction in the limit fracture thickness reduction rate. When the area ratio of retained austenite is 3.0% or more, the above effect becomes significant. Therefore, the area ratio of retained austenite is set to less than 3.0%. The area ratio of retained austenite is preferably less than 1.5%, and more preferably less than 1.0%.

[0173] The less the retained austenite, the better. Therefore, the area ratio of retained austenite may be 0%.

[0174] The area ratio of retained austenite can be measured by X-ray diffraction, EBSP (Electron Back Scattering Diffraction Pattern) analysis, magnetic measurement, etc. In the present embodiment, the area ratio of retained austenite is measured by X-ray diffraction.

[0175] In the determination of the area ratio of retained austenite based on X-ray diffraction of the present embodiment, first, in the section at the position 1 / 4 of the surface in the thickness direction of the hot-rolled steel plate, a sample is collected in a manner that the metal structure in the area of ​​more than 1 mm can be observed at any position in the rolling direction and the center in the direction orthogonal to the rolling direction and the thickness direction is observed. The sample is thickened by mechanical grinding and chemical grinding so that the position 1 / 4 of the surface in the thickness direction becomes the surface. For the above sample, an X-ray diffraction device (e.g., RINT-2500, Co-Kα ray produced by Rigaku) ​​is used to obtain the integrated intensity of 6 peaks, α(110), α(200), α(211), γ(111), γ(200), and γ(220). Next, the volume ratio of retained austenite is calculated from the above integrated intensity using the intensity average method. The obtained volume ratio of retained austenite is regarded as the area ratio of retained austenite.

[0176] Area ratio of ferrite: 15.0% or more and less than 60.0%

[0177] Ferrite is a structure formed when fcc phase transforms to bcc at a relatively high temperature. Ferrite has a high work hardening rate, so it has the effect of improving the balance of strength-ductility of hot-rolled steel sheets. In order to obtain the above effect, the area ratio of ferrite is set to 15.0% or more. It is preferably 20.0% or more, more preferably 25.0% or more, and even more preferably 30.0% or more.

[0178] On the other hand, since ferrite has low strength, if the area ratio is excessive, the desired strength cannot be obtained. Therefore, the ferrite area ratio is set to less than 60.0%, preferably 50.0% or less, and more preferably 45.0% or less.

[0179] Area ratio of pearlite: less than 5.0%

[0180] Pearlite is a thin-sheet metal structure in which cementite is precipitated in layers between ferrites. It is a softer metal structure than bainite and martensite. If the area ratio of pearlite is 5.0% or more, carbon is consumed by cementite contained in pearlite, and the strength of the remaining structures, i.e., martensite and bainite, decreases, and the desired strength cannot be obtained. Therefore, the area ratio of pearlite is set to less than 5.0%. The area ratio of pearlite is preferably 3.0% or less.

[0181] In order to improve the elongation flangeability of the hot-rolled steel sheet, the area ratio of pearlite is preferably reduced as much as possible, and the area ratio of pearlite is more preferably 0%.

[0182] Furthermore, the hot-rolled steel sheet of the present embodiment may contain, as the remaining structure other than retained austenite, ferrite and pearlite, a hard structure composed of one or more of bainite, martensite and tempered martensite with a total area ratio exceeding 32.0% and 85.0% or less.

[0183] The area ratio of ferrite and pearlite is determined by the following method. First, a sample is collected in the center of the direction orthogonal to the rolling direction and the plate thickness direction in such a way that the metal structure in the area 1 / 4 of the position from the surface in the plate thickness direction can be observed in the plate thickness section parallel to the rolling direction. The sample is designed to be able to observe a size of about 10 mm in the rolling direction. Then, after the above-mentioned sample section is polished and finished into a mirror surface, it is polished for 8 minutes at room temperature using colloidal silica with a particle size of 0.25 μm that does not contain an alkaline solution to remove the strain introduced into the surface of the sample. For an area of ​​200 μm or more at any position in the rolling direction of the above-mentioned sample section and 200 μm or more centered at 1 / 4 of the position from the surface in the plate thickness direction, the measurement is performed by electron backscatter diffraction method at a measurement interval of 0.1 μm in the rolling direction and the plate thickness direction to obtain crystal orientation information. In the above measurement, an EBSD analysis device consisting of a thermal field emission scanning electron microscope (e.g., JSM-7001F manufactured by JEOL) and an EBSD detector (e.g., DVC5 detector manufactured by TSL) was used. At this time, the vacuum degree in the EBSD analysis device was set to 9.6×10 -5Pa or less, the acceleration voltage was set to 15 kV, the irradiation current level was set to 13, and the irradiation level of the electron beam was set to 62. In addition, the number of observation fields was set to 5 fields.

[0184] Furthermore, a backscattered electron image is taken in the same field of view in which the above-mentioned crystal orientation information is obtained. In addition, in the shooting of the image, the acceleration voltage is set to 15 kV, the irradiation current level is set to 12-13, and the irradiation level of the electron beam is set to 62. The focal distance (WD: Waorking Distance) is set to 5 mm. According to the backscattered electron image and the above-mentioned crystal orientation information, ferrite and pearlite are identified. First, in the backscattered electron image, the grains in which cementite precipitates in the form of thin flakes are determined. In the backscattered electron image, cementite is observed as a white contrast. The cementite in the pearlite has a lamellar morphology, and the white contrast grains in the lamellar morphology observed at intervals of less than 1.0 μm are regarded as grains of pearlite. By calculating the area ratio of the grains, the area ratio of pearlite is obtained. Then, for grains other than the grains determined as pearlite, the obtained crystal orientation information was analyzed using the "Grain Average Misorientation: Grain Average Orientation Difference" function of the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device, and the region with a Grain Average Misorientation value of 1.0° or less was determined to be ferrite. At this time, the Grain Tolerance Angle was set to 15°, and the area ratio of the region determined to be ferrite was calculated, thereby obtaining the area ratio of ferrite.

[0185] The area ratio of the remaining structure is obtained by subtracting the area ratios of retained austenite, ferrite, and pearlite from 100%.

[0186] In addition, in the present embodiment, the rolling direction of the hot-rolled steel sheet is determined by the following method.

[0187] First, a test piece is collected in such a way that a cross section parallel to the surface of the hot-rolled steel sheet can be observed. The cross section of the test piece collected in the plate thickness direction is finished by mirror polishing and then observed using an optical microscope. The observation surface is set as a surface parallel to the plate surface at any depth in the range of 1 / 4 to 1 / 2 in the plate thickness direction, and in this observation surface, the direction parallel to the extension direction of the crystal grains is determined as the rolling direction.

[0188] Entropy value: 10.7 or above

[0189] Inverse difference normalized value: 1.020 or more

[0190] In order to suppress the generation of secondary shear planes, it is important to form a fracture surface after the shear planes are fully formed, and it is necessary to suppress the early generation of cracks from the tool tip during shearing. Therefore, it is important that the periodicity of the metal structure is low and the uniformity of the metal structure is high. In this embodiment, the generation of secondary shear planes is suppressed by controlling the Entropy value (E value) representing the periodicity of the metal structure and the Inverse difference normalized value (I value) representing the uniformity of the metal structure.

[0191] The E value represents the periodicity of the metal structure. When the brightness is arranged periodically due to the formation of a banded structure, that is, when the periodicity of the metal structure is high, the E value decreases. In the present embodiment, since it is necessary to form a metal structure with low periodicity, it is necessary to increase the E value. If the E value is lower than 10.7, secondary shear surfaces are easily generated. Starting from the periodically arranged structure, cracks are generated from the tip of the shearing tool at the very early stage of the shearing process to form a fracture surface, and then a shear surface is formed again. Thus, it is estimated that secondary shear surfaces are easily generated. Therefore, the E value is set to be greater than 10.7. Preferably, it is greater than 10.8, and more preferably, it is greater than 11.0. The higher the E value, the more preferred it is. There is no particular upper limit, but it can be set to less than 13.0, less than 12.5, or less than 12.0.

[0192] The I value represents the uniformity of the metal structure. The larger the area of ​​the region with a certain brightness, the higher the I value. A higher I value means that the uniformity of the metal structure is higher. In the present embodiment, it is necessary to form a metal structure with higher uniformity, and thus it is necessary to increase the I value. If the I value is lower than 1.020, due to the influence of the hardness distribution caused by the precipitates in the grains and the element concentration difference, cracks are generated from the tip of the shearing tool in the very early stage of the shearing process to form a fracture surface, and then a shear surface is formed again. Thus, it is estimated that secondary shear surfaces are easily generated. Therefore, the I value is set to be greater than 1.020. Preferably, it is greater than 1.025, and more preferably, it is greater than 1.030. The higher the I value, the more preferred it is. There is no particular upper limit, but it can also be set to less than 1.200, less than 1.150, or less than 1.100.

[0193] Cluster Shade value: -8.0×10 5 ~8.0×10 5

[0194] The Cluster Shade value (CS value) indicates the skewness of the metal structure. The CS value is positive when there are many points with brightness exceeding the average value and negative when there are many points with brightness below the average value relative to the average value of brightness in the image obtained by photographing the metal structure.

[0195] In the secondary electron image of the electron microscope, the brightness increases at the part with large surface unevenness of the observation object, and decreases at the part with small surface unevenness. The surface unevenness of the observation object is greatly affected by the particle size and intensity distribution in the metal structure. The CS value in this embodiment increases when the deviation of the intensity of the metal structure is large or the tissue unit is small, and decreases when the deviation of the intensity is small or the tissue unit is large.

[0196] In this embodiment, it is important to keep the CS value in a desired range close to 0. If the CS value is lower than -8.0×10 5 , the reduction rate of the ultimate fracture thickness of the hot-rolled steel sheet decreases. It can be inferred that this is because there are large grains in the metal structure, and these grains are preferentially destroyed during the ultimate deformation. Therefore, the CS value is set to -8.0×10 5 Above. Preferably -7.5×10 5 More preferably, -7.0×10 5 above.

[0197] On the other hand, if the CS value exceeds 8.0×10 5 , the reduction rate of the ultimate fracture thickness of the hot-rolled steel sheet decreases. It can be inferred that this is because the microscopic strength deviation in the metal structure is large, and the strain in the ultimate deformation is concentrated locally, making it easy to break. Therefore, the CS value is set to 8.0×10 5 Below. Preferably 7.5×10 5 Below, more preferably 7.0×10 5 the following.

[0198] The E value, I value, and CS value can be obtained by the following method.

[0199] In this embodiment, the shooting area of ​​the SEM image taken to calculate the E value, I value and CS value is set to 160 μm × 160 μm in the center of the direction perpendicular to the rolling direction and the plate thickness direction in the cross section parallel to the rolling direction, with the position 1 / 4 of the distance from the surface in the plate thickness direction as the center, and the number of observation fields is set to 5 fields. In the shooting of the SEM image, a SU-6600 Schottky electron gun manufactured by Hitachi High-Technologies Corporation is used, the emitter is set to tungsten, and the acceleration voltage is set to 1.5 kV. Based on the above settings, the SEM image is output at a magnification of 1000 times and 256 levels of grayscale.

[0200] Next, the obtained SEM image was cut into an area of ​​880×880 pixels (the observation area was 160μm×160μm in actual size), and the cut image was subjected to the smoothing process described in Non-Patent Document 3, with the limit magnification of contrast enhancement set to 2.0 and the block size set to 8×8. The smoothed SEM image was rotated counterclockwise from 0 to 179 degrees at every degree except 90 degrees, and an image was created at every degree, thereby obtaining a total of 179 images. Next, for each of these 179 images, the GLCM method described in Non-Patent Document 1 was used to collect the frequency values ​​of the brightness between adjacent pixels in a matrix form.

[0201] Let k be the rotation angle from the original image, and the matrix of 179 frequency values ​​collected by the above method is expressed as p k (k = 0 to 89, 91 to 179). For each image, the generated p k After summing up, a 256×256 matrix P normalized so that the sum of each component is 1 is calculated. Furthermore, the E value, I value, and CS value are calculated using the following equations (1) to (5) described in Non-Patent Document 2. In addition, the average value measured for all viewing fields is calculated.

[0202] P(i, j) in the following equations (1) to (5) is a gray level co-occurrence matrix, and the value of the i-th row and j-th column of the matrix P is recorded as P(i, j). In addition, as described above, since the 256×256 matrix P is used for calculation, if you want to emphasize this point, you can use the following equations (1) to (5).

[0203] (5) is corrected to the following equations (1') to (5'). Here, L in the following equation (2) is the number of grayscale levels (Quantization levels of grayscale) obtained by the SEM image. In this embodiment, as described above, the SEM image is output with 256 grayscale levels, so L is 256. i and j in the following equations (2) and (3) are natural numbers from 1 to the above L, and μ in the following equation (3) is x and μ y They are represented by the following formulas (4) and (5), respectively.

[0204] In the following equations (1') to (5'), the value of the i-th row and j-th column of the matrix P is denoted as P ij .

[0205] [Mathematical formula 6]

[0206] Entropy=-∑ i ∑ j P(i,j)log(P(i,j)) (1)

[0207] [Formula 7]

[0208]

[0209] [Mathematical formula 8]

[0210] Cluster Shade=∑ i ∑ j (i+j-μ x -μ y ) 3 P(i,j) (3)

[0211] [Mathematical formula 9]

[0212] μ x =∑ i ∑ j i (P(i,j)) (4)

[0213] [Formula 10]

[0214] μ y =∑ i ∑ j (P(i,j)) (5)

[0215] [Mathematical formula 11]

[0216]

[0217] [Mathematical formula 12]

[0218]

[0219] [Mathematical formula 13]

[0220]

[0221] [Formula 14]

[0222]

[0223] [Mathematical formula 15]

[0224]

[0225] Standard deviation of Mn concentration: 0.60 mass % or less

[0226] The standard deviation of the Mn concentration of the hot-rolled steel sheet of the present embodiment is 0.60% by mass or less. Thus, the hard phase can be evenly dispersed, and cracks can be prevented from being generated from the tip of the shearing tool at an extremely early stage of the shearing process. As a result, the generation of the secondary shear surface can be suppressed. The standard deviation of the Mn concentration is preferably 0.50% by mass or less, and more preferably 0.47% by mass or less. The lower limit of the standard deviation of the Mn concentration is preferably smaller from the viewpoint of suppressing excessive burrs, but due to the constraints of the manufacturing process, the actual lower limit is 0.10% by mass.

[0227] The standard deviation of Mn concentration can be obtained by the following method. First, a sample is collected in the center of the direction orthogonal to the rolling direction and the plate thickness direction in such a way that an area 1 / 4 of the distance from the surface in the plate thickness direction can be observed in a section parallel to the rolling direction. Although the sample also depends on the measuring device, it is set to a size of about 10 mm that can be observed in the rolling direction. Then, after the above-mentioned sample is mirror-polished, the standard deviation of the Mn concentration is measured using an electron probe microanalyzer (EPMA). The measurement conditions are to set the acceleration voltage to 15 kV, set the magnification to 5000 times, and measure the distribution image of 20 μm in the rolling direction of the sample and 20 μm in the plate thickness direction of the sample with the 1 / 4 position from the surface in the plate thickness direction as the center. More specifically, the measurement interval is set to 0.1 μm, and the Mn concentration is measured at more than 40,000 locations. Next, the standard deviation is calculated based on the Mn concentration obtained from all the measurement points, thereby obtaining the standard deviation of the Mn concentration.

[0228] Number density of Si-Al-Cr oxides with equivalent spherical radius of 0.500 μm or more on the surface: 2.0×10 3 Pieces / cm 2 the following

[0229] The number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm on the surface is 1.0×10 5 Pieces / cm 2 above

[0230] The present inventors have found that the corrosion resistance of a hot-rolled steel sheet can be improved by controlling the number density of oxides with an equivalent spherical radius of 0.500 μm or more and oxides with an equivalent spherical radius of 0.005 to 0.050 μm in Si—Al—Cr oxides formed on the surface within a desired range.

[0231] On the surface, if the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more exceeds 2.0×10 3 Pieces / cm 2, the electrochemical reaction between the solution and the steel sheet is partially hindered during the chemical conversion treatment, and the zinc phosphate film will not adhere to the steel sheet, thereby deteriorating the corrosion resistance of the hot-rolled steel sheet. Therefore, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more on the surface is set to 2.0×10 3 Pieces / cm 2 Below. Preferably 1.8×10 3 Pieces / cm 2 Below, more preferably 1.5×10 3 Pieces / cm 2 the following.

[0232] The number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more can also be set to 0.1×10 3 Pieces / cm 2 above.

[0233] On the surface, if the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm is less than 1.0×10 5 Pieces / cm 2 , the corrosion resistance of the hot-rolled steel sheet deteriorates. The mechanism is still uncertain, but it is believed that the reason is that the zinc phosphate film is easy to adhere to the tiny Si-Al-Cr oxides due to the anchoring effect brought about by the increase in surface area, rather than the effect of hindering the electrochemical reaction. Therefore, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm on the surface is set to 1.0×10 5 Pieces / cm 2 More than 3.0×10 5 Pieces / cm 2 More preferably, 5.0×10 5 Pieces / cm 2 above.

[0234] The number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm can also be set to 100.0×10 5 Pieces / cm 2 the following.

[0235] In addition, in the present embodiment, it is not necessary to limit the number density of Si-Al-Cr oxides with an equivalent spherical radius of more than 0.050 μm and less than 0.500 μm and the number density of Si-Al-Cr oxides with an equivalent spherical radius of less than 0.005 μm on the surface. This is because, in the hot-rolled steel sheet manufactured by the chemical composition of the present embodiment and the manufacturing method described later, Si-Al-Cr oxides with an equivalent spherical radius of more than 0.050 μm and less than 0.500 μm and Si-Al-Cr oxides with an equivalent spherical radius of less than 0.005 μm are not formed in such an amount that adversely affects the characteristics of the hot-rolled steel sheet of the present embodiment.

[0236] The number density of Si—Al—Cr oxides on the surface was measured by the following method.

[0237] The sample is cut out from the hot-rolled steel plate in such a way that the surface in the thickness direction becomes the observation surface. After the observation surface is degreased at 60°C for 60 seconds using FC-E6403 produced by Nippon Parkerizing, it is immersed in acetone and ultrasonically cleaned for 90 seconds. Then, more than 10 fields of view are observed at a magnification of 3000 times. The composition of the precipitate can be measured by EDS (energy dispersive X-ray spectrometer). Among the precipitates, among the precipitates containing Si, Al, Cr and O, the area with an equivalent spherical radius of 0.500μm or more and the area of ​​0.005 to 0.050μm are selected, and their number is counted in each field of view, and divided by the measured area, thereby obtaining the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500μm or more and the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050μm.

[0238] Furthermore, when EDS analysis was performed on the precipitate and 10 atomic % or more of Si, Cr, and O were detected respectively and 5 atomic % or more of Al was detected, the precipitate was regarded as Si—Al—Cr oxide.

[0239] In addition, when the hot-rolled steel sheet has oxide scale on the surface, the sample was subjected to pickling treatment under the following conditions and then subjected to the above-mentioned surface treatment.

[0240] The pickling treatment can be carried out by conventional methods, for example, by immersing in hydrochloric acid with a hydrochloric acid concentration of 3 to 10% by volume at a temperature of 85°C to 98°C for 20 seconds to 300 seconds. In addition, pickling can be carried out once or multiple times as needed. The above-mentioned pickling time (20 seconds to 300 seconds) refers to the time of the pickling when only one pickling is carried out, and refers to the total time of these picklings when multiple picklings are carried out. By setting the pickling temperature to above 85°C, the oxides on the surface can be fully removed, so it is preferred. The upper limit of the pickling temperature is not particularly limited, but in reality it is about 98°C. When the pickling time exceeds 300 seconds, the surface roughness becomes too coarse, the surface properties deteriorate, and the unevenness remaining after cold rolling produces a notch-like effect, which sometimes deteriorates the bendability of the hot-rolled steel sheet. The upper limit of the pickling time is preferably 200 seconds.

[0241] In the case where the hot-rolled steel sheet has a surface treatment film such as a plating layer and a coating, the surface of the base obtained after removing the surface treatment film is subjected to the above-mentioned pickling treatment and then provided with the above-mentioned surface treatment. The method for removing the surface treatment film can be appropriately selected according to the type of the surface treatment film within the range that does not affect the surface roughness of the base. For example, in the case where the surface treatment film is a zinc coating such as electrogalvanizing, electroplating Zn-Ni alloy, hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip Zn-Al alloy, hot-dip Zn-Al-Mg alloy, and hot-dip Zn-Al-Mg-Si alloy, the zinc coating can be dissolved using dilute hydrochloric acid to which a corrosion inhibitor is added. In this way, only the zinc coating can be peeled off from the steel sheet. The so-called corrosion inhibitor is an additive used to suppress the change in roughness caused by preventing excessive dissolution of the base. For example, a corrosion inhibitor "Corrosion Inhibitor for Hydrochloric Acid Pickling produced by Asahi Chemical Industries, Ltd." can be added to hydrochloric acid diluted to 5% by volume in a concentration of 0.6 g / L. No.700BK". In addition, when the surface treatment film is an aluminum coating such as hot-dip aluminum, according to the description of JIS G 3314:2019, it is immersed in a dilute hydrochloric acid aqueous solution to which a sodium hydroxide aqueous solution and hexamethylenetetramine are added in sequence, and the immersion is performed until the foaming caused by the dissolution of the coating disappears, thereby dissolving the Al coating. In addition, when the surface treatment film is electrophoretic coating, a stripping agent (NEOREVER SP-751: manufactured by Sancai Chemical Co., Ltd.) is used to strip the electrophoretic coating.

[0242] Tensile strength properties

[0243] The tensile strength characteristics (tensile strength, total elongation) of the mechanical properties of the hot-rolled steel sheet were evaluated in accordance with JIS Z 2241: 2011. The test piece was set to the No. 5 test piece of JIS Z 2241: 2011. The sampling position of the test piece was set to the position 1 / 4 of the distance from the end face in the direction orthogonal to the rolling direction and the plate thickness direction, and the plate width direction was set to the length direction of the test piece.

[0244] The tensile strength of the hot-rolled steel sheet of this embodiment is 980 MPa or more. Preferably, it is 1000 MPa or more. If the tensile strength is lower than 980 MPa, the application parts are limited and the contribution to the lightweighting of the vehicle body is small. The upper limit does not need to be particularly limited, but from the perspective of suppressing die wear, it can also be set to 1780 MPa.

[0245] In addition, the total elongation of the hot-rolled steel sheet of the present embodiment is preferably set to 10.0% or more, and the product of the tensile strength and the total elongation (TS×El) is preferably set to 13000 MPa·% or more. The total elongation is more preferably set to 11.0% or more, and further preferably set to 13.0% or more. In addition, the product of the tensile strength and the total elongation is more preferably set to 14000 MPa·% or more, and further preferably set to 15000 MPa·%MPa or more. By setting the total elongation to 10.0% or more and setting the product of the tensile strength and the total elongation to 13000 MPa·% or more, the applicable parts are not limited, which can greatly contribute to the lightweighting of the vehicle body.

[0246] Plate thickness

[0247] The plate thickness of the hot-rolled steel plate of the present embodiment is not particularly limited, but can also be set to 0.5 to 8.0 mm. When the plate thickness of the hot-rolled steel plate is less than 0.5 mm, it is sometimes difficult to ensure the rolling end temperature, and the rolling load is too large, making hot rolling difficult. Therefore, the plate thickness of the hot-rolled steel plate of the present embodiment can also be set to more than 0.5 mm. Preferably, it is more than 1.2 mm or more than 1.4 mm. On the other hand, when the plate thickness exceeds 8.0 mm, it becomes difficult to refine the metal structure, and it is sometimes difficult to obtain the above-mentioned metal structure. Therefore, the plate thickness can also be set to less than 8.0 mm. Preferably, it is less than 6.0 mm.

[0248] Plating

[0249] The hot-rolled steel sheet with the above-mentioned chemical composition and metal structure of the present embodiment is for the purpose of improving corrosion resistance, etc., and can also form a surface-treated steel sheet by having a coating on the surface. The coating can be an electroplated layer or a hot-dip coating. As the electroplated layer, examples include electrogalvanizing and electroplating Zn-Ni alloy. As the hot-dip coating, examples include hot-dip galvanizing, alloyed hot-dip galvanizing, hot-dip aluminum plating, hot-dip Zn-Al alloy plating, hot-dip Zn-Al-Mg alloy plating, hot-dip Zn-Al-Mg-Si alloy plating, etc. There are no special restrictions on the coating adhesion amount, and it can be the same as before. In addition, by implementing appropriate chemical conversion treatment (such as coating and drying of chromium-free chemical conversion treatment liquid of silicate system) after plating, it is also possible to further improve corrosion resistance.

[0250] Manufacturing conditions

[0251] A preferred method for producing the hot-rolled steel sheet having the above-mentioned chemical composition and metal structure according to the present embodiment is as follows.

[0252] In the preferred method for manufacturing the hot-rolled steel sheet of the present embodiment, the following steps (1) to (11) are performed in sequence. In addition, the slab temperature and the steel sheet temperature in the present embodiment refer to the surface temperature of the slab and the surface temperature of the steel sheet. In addition, stress refers to the tension applied in the rolling direction of the steel sheet.

[0253] (1) After the slab is held in a temperature range of 700 to 850° C. for 900 seconds or more, it is heated again and held in a temperature range of 1100° C. or more for 6000 seconds or more.

[0254] (2) Descaling is performed at least once in a temperature range of 1200°C or higher before rough rolling, and descaling is performed at least twice in a temperature range of 1150°C or higher during rough rolling, and the maximum value of the total reduction ratio between descaling in the temperature range of 1150°C or higher is set to 40% or higher.

[0255] (3) The maximum temperature from the final stage of rolling at a rolling reduction exceeding 20% ​​to descaling after the completion of rough rolling is set to 1130° C. or less.

[0256] (4) Hot rolling is performed so that the total reduction ratio in the temperature range of 850 to 1100° C. becomes 90% or more.

[0257] (5) A stress of 170 kPa or more is applied to the steel sheet from the end of the rolling before the final stage of hot rolling to the start of the final stage of rolling.

[0258] (6) The rolling reduction rate in the final stage of hot rolling is set to 8% or more, and the hot rolling is completed so that the rolling end temperature Tf is 900°C or more and lower than 1010°C.

[0259] (7) From the end of the final stage of hot rolling until the steel sheet is cooled to 800° C., a stress of less than 200 kPa is applied to the steel sheet.

[0260] (8) After the hot rolling is completed, the steel is cooled to a temperature range of 600 to 780° C. at an average cooling rate of 50° C. / s or more.

[0261] (9) In the temperature range of 600 to 780°C, slow cooling is performed at an average cooling rate of less than 5°C / s for 2.0 seconds or more.

[0262] (10) After the slow cooling is completed, cooling is performed so that the average cooling rate in the temperature range of 450 to 600° C. becomes 30° C. / s or more and less than 50° C. / s.

[0263] (11) Cooling is performed so that the average cooling rate in the temperature range from the coiling temperature to 450°C becomes 50°C / s or more.

[0264] (12) Coiling is performed in a temperature range of 350°C or lower.

[0265] By adopting the above-mentioned production method, a hot-rolled steel sheet having high strength and ultimate fracture thickness reduction rate, as well as excellent ductility, shear workability and corrosion resistance can be stably produced.

[0266] (1) Slab, slab temperature during hot rolling, and holding time

[0267] The slabs to be used for hot rolling may be slabs obtained by continuous casting, slabs obtained by casting and blooming, etc. In addition, materials subjected to hot working or cold working may be used as needed.

[0268] The slab for hot rolling is preferably kept in a temperature range of 700 to 850°C for more than 900 seconds when the slab is heated, and then heated again and kept in a temperature range of 1100°C or more for more than 6000 seconds. In addition, during the holding in the temperature range of 700 to 850°C, the temperature of the steel plate may be varied within the temperature range or may be set constant. In addition, during the holding at 1100°C or more, the temperature of the steel plate may be varied within the temperature range or may be set constant.

[0269] In the austenite transformation in the temperature range of 700-850°C, Mn is distributed between ferrite and austenite to extend the transformation time, so that Mn can diffuse along the ferrite region. As a result, the uneven Mn microsegregation in the slab can be eliminated, and the standard deviation of the Mn concentration can be significantly reduced. In addition, by maintaining the temperature range above 1100°C for more than 6000 seconds, the standard deviation of the Mn concentration can be significantly reduced.

[0270] Hot rolling preferably uses a reversible rolling mill or a tandem rolling mill as a multi-pass rolling. In particular, from the perspective of industrial productivity and the stress load on the steel plate during rolling, it is more preferred that the hot rolling uses a tandem rolling mill in at least the final two stages. Hot rolling is a process including rough rolling and finish rolling, and multiple (stage) rolling is performed for each. Rough rolling is a process of rolling the slab to a minimum of 25 mm, and finish rolling is a process of rolling the rough-rolled plate to a target plate thickness.

[0271] (2) Descaling conditions before rough rolling, descaling during rough rolling, and rolling conditions

[0272] Before rough rolling, descaling is preferably performed at least once in a temperature range of 1200°C or more. By performing descaling at least once in a temperature range of 1200°C or more before rough rolling, the primary scale formed in the heating furnace can be removed, and the occurrence of subsequent poor scale removal can be suppressed. As a result, on the surface of the hot-rolled steel sheet, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more can be preferably controlled. The upper limit of the number of descaling in the temperature range of 1200°C or more is not particularly limited, but can also be set to 5 times or less.

[0273] During rough rolling, multiple rolling and descaling are performed. During rough rolling, descaling is performed between rolling and rolling or after multiple rolling. In the present embodiment, descaling is preferably performed twice or more in a temperature range of 1150°C or more during rough rolling, and the maximum value of the total reduction ratio between descaling in the temperature range of 1150°C or more is set to 40% or more. By performing descaling twice or more in a temperature range of 1150°C or more, the thickness of the scale formed in the front section of rough rolling can be reduced, or by removing the scale, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more can be preferably controlled on the surface of the hot-rolled steel sheet. In addition, by setting the maximum value of the total reduction ratio between descaling in the temperature range of 1150°C or more to 40% or more, the descaling effect can be improved, and the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more can be preferably controlled on the surface of the hot-rolled steel sheet.

[0274] In order to set the maximum value of the total reduction ratio of the descaling interval in the temperature range of 1150°C or above to 40% or above, for example, rolling with a reduction ratio of 40% or above is performed once in a certain descaling interval in the temperature range of 1150°C or above, or rolling is performed multiple times in such a way that the total reduction ratio is 40% or above.

[0275] When the plate thickness before the nth descaling in the temperature range above 1150°C is set to t0 and the outlet plate thickness after the n+1th descaling in the temperature range above 1150°C is set to t1, the total reduction rate between each descaling in the temperature range above 1150°C can be expressed by {(t0-t1) / t0}×100(%). Between the nth descaling and the n+1th descaling, rolling may be performed only once or multiple times. Descaling can be performed by water jetting.

[0276] (3) Temperature conditions during and after rough rolling

[0277] In rough rolling, the maximum temperature from the final stage of rolling with a reduction rate exceeding 20% ​​to descaling after the end of rough rolling is preferably set to 1130°C or less. After rough rolling, descaling is performed to remove the scale generated during rough rolling. In addition, after the final stage of rough rolling, the temperature of the steel plate rises due to reflux heat exchange from the inside of the steel plate. In the present embodiment, in rough rolling, the maximum temperature of the steel plate temperature that rises due to reflux heat exchange is preferably controlled to be below 1130°C during the period from the final stage of rolling with a reduction rate exceeding 20% ​​to descaling after the end of rough rolling. In rough rolling, by setting the maximum temperature from the final stage of rolling with a reduction rate exceeding 20% ​​to descaling after the end of rough rolling to 1130°C or less, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm can be preferably controlled.

[0278] Furthermore, for the purpose of uniform heating of the steel sheet, even when the steel sheet temperature is increased by heating during the period from the final stage of rolling with a reduction ratio exceeding 20% ​​to descaling after the completion of rough rolling, the maximum temperature is preferably controlled to be 1130°C or less.

[0279] In addition, the "final section of rolling with a reduction ratio exceeding 20%" mentioned here is not limited to the final rolling of the finishing rolling. For example, if the final rolling of the finishing rolling has a reduction ratio of 20% or less, as long as the reduction ratio of the rolling before the final section exceeds 20%, the rolling before the final section is the "final section of rolling with a reduction ratio exceeding 20%".

[0280] (4) Total reduction ratio of hot rolling: 90% or more in the temperature range of 850-1100°C

[0281] By performing hot rolling with a total reduction ratio of 90% or more in the temperature range of 850 to 1100°C, the recrystallized austenite grains can be mainly refined, while promoting the accumulation of strain energy in the non-recrystallized austenite grains. In addition, while promoting the recrystallization of austenite, the atomic diffusion of Mn can also be promoted, reducing the standard deviation of the Mn concentration. Therefore, it is preferred to perform hot rolling with a total reduction ratio of 90% or more in the temperature range of 850 to 1100°C.

[0282] In addition, the hot rolling mentioned here includes rough rolling and finish rolling.

[0283] In addition, the so-called reduction rate in the temperature zone of 850 to 1100°C can be expressed by {(t0-t1) / t0}×100(%) when the entrance plate thickness before the initial rolling in the rolling in this temperature zone is set to t0 and the exit plate thickness after the final rolling in the rolling in this temperature zone is set to t1.

[0284] (5) Stress applied to the steel sheet from the end of the final rolling stage to the start of the final rolling stage of hot rolling: 170 kPa or more

[0285] It is preferred that a stress of 170 kPa or more be applied to the steel sheet from the end of the final rolling stage to the start of the final rolling stage. This can reduce the number of grains having a crystal orientation of {110}<001> in the recrystallized austenite after the final rolling stage. <001> This is a crystal orientation that is difficult to recrystallize, so by suppressing the formation of this crystal orientation, recrystallization based on the final stage of rolling can be effectively promoted. As a result, the banded structure of the hot-rolled steel sheet is improved, the periodicity of the metal structure is reduced, and the E value is increased.

[0286] The rolling before the final stage of hot rolling mentioned here refers to the rolling before the final stage of finish rolling. For example, when finish rolling is performed in 7 passes of F1, F2 ... F6, and F7, it refers to the 6th pass (F6).

[0287] When the stress applied to the steel sheet is less than 170 kPa, the E value may not be set to a desired value. The stress applied to the steel sheet is more preferably 190 kPa or more.

[0288] The so-called stress applied to the steel plate refers to the tension applied in the length direction of the steel plate, which can be controlled by adjusting the roller rotation speed in tandem rolling and can be calculated by dividing the load in the rolling direction measured by the rolling stand by the cross-sectional area of ​​the steel plate passing through the plate.

[0289] (6) The final stage of hot rolling has a reduction ratio of 8% or more, and the hot rolling end temperature Tf is 900°C or more and less than 1010°C.

[0290] The reduction rate in the final stage of hot rolling is preferably set to 8% or more, and the hot rolling end temperature Tf is preferably set to 900°C or more. By setting the reduction rate in the final stage of hot rolling to 8% or more, the recrystallization caused by the reduction in the final stage can be promoted. As a result, the banded structure of the hot-rolled steel sheet is improved, the periodicity of the metal structure is reduced, and the E value is increased. By setting the hot rolling end temperature Tf to 900°C or more, the excessive increase in the number of ferrite nucleation sites in austenite can be suppressed. As a result, the formation of ferrite in the final structure (the metal structure of the hot-rolled steel sheet after manufacture) can be suppressed, and a high-strength hot-rolled steel sheet can be obtained. In addition, by setting Tf to less than 1010°C, the coarsening of the austenite grain size can be suppressed, the periodicity of the metal structure can be reduced, and the E value can be set to a desired value.

[0291] (7) Stress applied to the steel sheet from the end of the final stage of hot rolling to the cooling of the steel sheet to 800°C: less than 200 kPa

[0292] From the end of the final stage of hot rolling until the steel plate is cooled to 800°C, it is preferred to apply a stress of less than 200 kPa to the steel plate. By applying a stress of less than 200 kPa to the steel plate, the recrystallization of austenite proceeds preferentially in the rolling direction, and the periodic increase of the metal structure can be suppressed. As a result, the E value can be set to a desired value. The stress applied to the steel plate is more preferably less than 180 kPa.

[0293] (8) Accelerate cooling to a temperature range of 600 to 780°C at an average cooling rate of 50°C / s or more

[0294] After hot rolling, accelerated cooling to a temperature range of 780°C or lower at an average cooling rate of 50°C / s or higher can suppress the formation of ferrite and pearlite with small precipitation strengthening amounts. This can improve the strength of the hot-rolled steel sheet.

[0295] The average cooling rate referred to here refers to the value obtained by dividing the temperature drop of the steel plate from the start of accelerated cooling (when the steel plate is introduced into the cooling device) to the end of accelerated cooling (when the steel plate is taken out of the cooling device) by the time required from the start of accelerated cooling to the end of accelerated cooling.

[0296] There is no particular upper limit on the cooling rate, but if the cooling rate is increased, the cooling equipment will be large-scale, which will increase the equipment cost. Therefore, considering the equipment cost, it is preferably 300°C / s or less. In addition, in order to perform the slow cooling described later, the cooling stop temperature of the accelerated cooling can be set to 600°C or more.

[0297] (9) In the temperature range of 600 to 780°C, slow cooling is performed with an average cooling rate of less than 5°C / s for more than 2.0 seconds.

[0298] By performing slow cooling at an average cooling rate of less than 5°C / s for 2.0 seconds or more in a temperature range of 600 to 780°C, precipitation-strengthened ferrite can be sufficiently precipitated. Thus, both strength and ductility of the hot-rolled steel sheet can be achieved.

[0299] The average cooling rate referred to here is a value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of the accelerated cooling to the slow cooling stop temperature by the time required from the stop of the accelerated cooling to the stop of the slow cooling.

[0300] The time for slow cooling is preferably 3.0 seconds or more. The upper limit of the time for slow cooling is determined according to the equipment layout, but can be roughly set to less than 10.0 seconds. In addition, the lower limit of the average cooling rate of slow cooling is not particularly set, but heating without cooling is accompanied by a large investment in equipment, so it can also be set to 0°C / s or more.

[0301] (10) After the slow cooling is completed, cooling is performed so that the average cooling rate in the temperature range of 450 to 600°C becomes 30°C / s or more and less than 50°C / s.

[0302] After the above slow cooling is completed, it is preferred to cool the steel sheet in such a way that the average cooling rate in the temperature range of 450 to 600°C is 30°C / s or more and less than 50°C / s. By setting the average cooling rate in the above temperature range to 30°C / s or more and less than 50°C / s, the CS value can be set to a desired value. When the average cooling rate is 50°C / s or more, a flat lath structure with low brightness is easily generated, and the CS value is less than -8.0×10 5 When the average cooling rate is lower than 30°C / s, the concentration of carbon in the non-transformed part is promoted, the strength of the hard structure increases, and the strength difference with the soft structure increases, so the CS value exceeds 8.0×10 5 .

[0303] In addition, the so-called average cooling rate mentioned here refers to the value obtained by dividing the temperature drop range of the steel plate from the cooling stop temperature of slow cooling with an average cooling rate of less than 5°C / s to the cooling stop temperature of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s by the time required from the stop of slow cooling with an average cooling rate of less than 5°C / s to the stop of cooling with an average cooling rate of 30°C / s or more and less than 50°C / s.

[0304] (11) Average cooling rate in the temperature range from coiling temperature to 450°C: 50°C / s or more

[0305] In order to suppress the area ratio of pearlite and retained austenite and obtain desired strength and formability, the average cooling rate in the temperature range from the coiling temperature to 450° C. is preferably set to 50° C. / s or more. This can make the parent phase structure hard.

[0306] In addition, the average cooling rate mentioned here refers to the value obtained by dividing the temperature drop range of the steel plate from the cooling stop temperature of cooling at an average cooling rate of 30°C / s or more and less than 50°C / s to the coiling temperature by the time required from the stop of cooling at an average cooling rate of 30°C / s or more and less than 50°C / s to coiling.

[0307] (12) Coiling temperature: below 350°C

[0308] The coiling temperature is set to 350° C. or less. By setting the coiling temperature to 350° C. or less, the precipitation amount of iron carbides is reduced, and the deviation of the hardness distribution in the hard phase can be reduced. As a result, the I value can be increased, and the generation of secondary shear planes can be suppressed.

[0309] Example

[0310] Next, the effects of one embodiment of the present invention are described in more detail through an embodiment, but the conditions in the embodiment are a conditional example adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this conditional example. The present invention can adopt a variety of conditions within the scope of achieving the purpose of the present invention without departing from the gist of the present invention.

[0311] Steels having the chemical compositions shown in Tables 1 and 2 were melted and continuously cast to produce slabs having a thickness of 240 to 300 mm. The obtained slabs were used to produce hot-rolled steel sheets shown in Tables 5A to 6B under the production conditions shown in Tables 3A to 4B.

[0312] The average cooling rate of the slow cooling was set to be lower than 5°C / s. In addition, the coiling temperatures described in Tables 4A and 4B are 50°C as the lower limit of measurement, so the actual coiling temperature in the example described as 50°C is 50°C or lower.

[0313] For the obtained hot-rolled steel sheet, the area ratio of the metal structure, E value, I value, CS value, standard deviation of Mn concentration, number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more and number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm on the surface, tensile strength TS and total elongation El were obtained by the above method. The obtained measurement results are shown in Tables 5A to 6B.

[0314] Evaluation method of characteristics of hot-rolled steel sheets

[0315] Tensile properties

[0316] When the tensile strength TS is 980 MPa or more, the total elongation El is 10.0% or more, and the tensile strength TS×total elongation El is 13000 MPa·% or more, the hot-rolled steel sheet is judged as qualified as having high strength and excellent ductility. If any one of the above conditions is not satisfied, the hot-rolled steel sheet is judged as not having high strength and excellent ductility and is unqualified.

[0317] Limit fracture thickness reduction rate

[0318] The ultimate fracture thickness reduction rate of the hot-rolled steel sheets was evaluated by a tensile test.

[0319] The tensile test was performed in the same manner as that used to evaluate the tensile properties. When the plate thickness before the tensile test was set to t1 and the minimum plate thickness in the central portion of the tensile test piece in the width direction (short side direction) after fracture was set to t2, the value of (t1-t2)×100 / t1 was calculated to obtain the limit fracture plate thickness reduction rate. Five tensile tests were performed, and the average of the three tests, excluding the maximum and minimum values ​​of the limit fracture plate thickness reduction rate, was calculated to obtain the limit fracture plate thickness reduction rate.

[0320] When the limit breaking thickness reduction rate is 60.0% or more, the hot rolled steel sheet is judged as having a high limit breaking thickness reduction rate and is qualified. On the other hand, when the limit breaking thickness reduction rate is less than 60.0%, the hot rolled steel sheet is judged as not having a high limit breaking thickness reduction rate and is unqualified.

[0321] Shear processability (secondary shear surface evaluation)

[0322] The shear workability of the hot-rolled steel sheets was evaluated by a punching test.

[0323] Three punching holes were made for each example with a hole diameter of 10 mm, a clearance of 10%, and a punching speed of 3 m / s. Next, the cross section of the punching hole at right angles to the rolling direction and the cross section parallel to the rolling direction were buried in resin, and the cross-sectional shape was photographed using a scanning electron microscope. In the obtained observation photograph, it can be observed that Figure 1 or Figure 2 In addition, Figure 1 This is an example of the sheared end surface of the hot-rolled steel sheet of the present invention. Figure 2 This is an example of a sheared end surface of a hot-rolled steel sheet of a comparative example. Figure 1 It is the shear end surface of collapsed edge-shear surface-fracture surface-burr. On the other hand, Figure 2 The shear end surface is a collapsed edge-shear surface-fracture surface-shear surface-fracture surface-burr. Here, the collapsed edge refers to the area of ​​the R-shaped smooth surface, the shear surface refers to the area of ​​the punched end surface separated by shear deformation, the fracture surface refers to the area of ​​the punched end surface separated by cracks generated near the blade tip, and the burr refers to the surface with protrusions protruding from the lower surface of the hot-rolled steel plate.

[0324] In the obtained shear end faces, two faces perpendicular to the rolling direction and two faces parallel to the rolling direction, for example, when observing Figure 2 In the case of the shear plane-fracture plane-shear plane shown in FIG. 1 , it is determined that a secondary shear plane is formed. Four planes of each punched hole, a total of 12 planes, are observed. If none of the planes with secondary shear planes appear, it is determined to be qualified as a hot-rolled steel sheet with excellent shear workability, and is recorded as "no" in the table. On the other hand, even if one secondary shear plane is formed, it is determined to be unqualified as a hot-rolled steel sheet that does not have excellent shear workability, and is recorded as "yes" in the table.

[0325] Corrosion resistance

[0326] A 70 mm × 40 mm sample was collected from the hot-rolled steel plate after pickling, and after zinc phosphate treatment (SD5350 system: standard made by Japan Paint Industrial Coding Co., Ltd.), a scanning electron microscope (SEM) was used to observe three locations (central part and both ends) along the length direction of the test piece at a magnification of 1000 times. The pickling conditions were set to the same conditions as the above pickling treatment.

[0327] When the coverage of the chemical conversion treatment crystals relative to the surface area is 98% or more, it is judged as a hot-rolled steel sheet with excellent corrosion resistance and is judged to be qualified. On the other hand, when the coverage of the chemical conversion treatment crystals relative to the surface area is less than 98%, it is judged as not a hot-rolled steel sheet with excellent corrosion resistance and is judged to be unqualified.

[0328]

[0329]

[0330]

[0331]

[0332] Table 44A

[0333]

[0334] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.

[0335] Table 4B

[0336]

[0337] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.

[0338]

[0339]

[0340] Table 6A

[0341]

[0342] Underlining indicates that the feature is outside the scope of the present invention or is not preferred.

[0343] Table 6B

[0344]

[0345] Underlining indicates that the feature is outside the scope of the present invention or is not preferred.

[0346] As can be seen from Tables 5A to 6B, the hot-rolled steel sheets of the examples of the present invention have high strength and ultimate fracture thickness reduction rate, as well as excellent ductility, shear workability, and corrosion resistance.

[0347] On the other hand, it is found that one or more characteristics of the hot-rolled steel sheets of the comparative examples are deteriorated.

[0348] Industrial Applicability

[0349] According to the above aspects of the present invention, it is possible to provide a hot-rolled steel sheet having high strength and ultimate fracture thickness reduction rate, as well as excellent ductility, shear workability, and corrosion resistance.

[0350] The hot-rolled steel sheet of the present invention is suitable as an industrial base material for automobile components, machine structural components, and building components.

Claims

1. A hot rolled steel plate, characterized in that: The chemical composition contains by mass %: C:0.050~0.250%、 Si: 0.40-1.00%, Mn: 1.00~1.50%, Sol.Al: 0.100~0.500%, Cr:0.50~2.00%、 P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Ti: 0~0.500%, Nb: 0~0.500%, V:0~0.500%、 Cu: 0-2.00%, Mo: 0-1.00%, Ni: 0-2.00%, B:0~0.0100%、 Ca: 0~0.0200%, Mg: 0~0.0200%, REM: 0~0.1000%、 Bi: 0~0.0200%, As: 0~0.100%, Zr:0~1.00%、 Co: 0-1.00%, Zn: 0-1.00%, W: 0-1.00%, and Sn: 0~0.05%, The remainder includes Fe and impurities; Satisfying the following equations (A) and (B), The metal structure at a position 1 / 4 from the surface in the thickness direction is expressed in area %, Retained austenite is less than 3.0%, Ferrite is 15.0% or more and less than 60.0%, Pearlite is less than 5.0%, The entropy value expressed by the following formula (1) obtained by analyzing the SEM image of the metal structure using the gray level co-occurrence matrix method is 10.7 or more. The inverse difference normalized value expressed by the following formula (2) is 1.020 or more. The Cluster Shade value expressed by the following formula (3) is -8.0×10 5 ~8.0×10 5 , The standard deviation of the Mn concentration is 0.60 mass % or less; In the surface, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.500 μm or more is 2.0×10 3 Pieces / cm 2 Below, the number density of Si-Al-Cr oxides with an equivalent spherical radius of 0.005 to 0.050 μm is 1.0×10 5 Pieces / cm 2 above; 0.060%≤Ti+Nb+V≤0.500%(A) Zr+Co+Zn+W≤1.00%(B) Wherein, each element symbol in the formula (A) and (B) represents the content of the element in mass %, and 0% is entered when the element is not contained; Here, P(i, j) in the following equations (1) to (5) is a gray level co-occurrence matrix, L in the following equation (2) is the number of gray levels obtained in the SEM image, i and j in the following equations (2) and (3) are natural numbers from 1 to L, and μ in the following equation (3) is x and μ y They are represented by the following formulas (4) and (5) respectively; [Mathematical formula 1] Entropy=-Σ i Σ j P(i,j)log(P(i,j)) (1) [Mathematical formula 2] [Mathematical formula 3] Cluster Shade = Σ i Σ j (i + j - μ x - μ y ) 3 P(i, j) (3)[Equation 4] μ x ∑ i ∑ j i(P(i,j)) (4) [Formula 5] μ y ∑ i ∑ j j(P(i,j)) (5)。 2. The hot rolled steel sheet according to claim 1, characterized in that: The chemical composition contains, in mass%, a Ti: 0.001~0.500%, Nb: 0.001~0.500%, V:0.001~0.500%、 Cu: 0.01-2.00%, Mo: 0.01~1.00%, Ni: 0.02-2.00%, B:0.0001~0.0100%、 Ca: 0.0005~0.0200%, Mg: 0.0005~0.0200%, REM: 0.0005~0.1000%、 Bi: 0.0005~0.0200%, As: 0.001~0.100%, Zr:0.01~1.00%、 Co: 0.01~1.00%, Zn: 0.01~1.00%, W: 0.01 to 1.00%, and Sn: 0.01 to 0.05% of one or more kinds thereof.

Citation Information

Patent Citations

  • Positioning device

    JP2022174630A

  • Hot-rolled steel sheet and production method therefor, cold-rolled steel sheet and production method therefor, production method for cold-rolled annealed steel sheet, and production method for hot-dip galvanized steel sheet

    WO2020044445A1